The Future of the Law of the Sea Bridging Gaps Between National, Individual and Common Interests - Andreone, Gemma (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 4.0 license. It explores the diverse phenomena which are challenging the international law of the sea today, using the unique perspective of a simultaneous analysis of the national, individual and common interests at stake. This perspective, which all the contributors bear in mind when treating their own topic, also constitutes a useful element in the effort to bring today's legal complexity and fragmentation to a homogenous vision of the sustainable use of the marine environment and of its resources, and also of the international and national response to maritime crimes. The volume analyzes the relevant legal frameworks and recent developments, focusing on the competing interests which have influenced State jurisdiction and other regulatory processes. An analysis of the competing interests and their developments allows us to identify actors and relevant legal and institutional contexts, retracing how and when these elements have changed over time.